Cytokine production by human colonic intraepithelial lymphocytes in controls and ulcerative colitis. - Hoang, P; Dalton, H; de Silv, H; Jewell, D (1994)
Using an ELISA technique, concentrations of gamma-interferon and interleukin-2 were assayed in the supernatants of colonic intraepithelial lymphocytes cultured with or without phytohaemagglutinin (PHA). IntraepitheHal lymphocytes produced low concentrations of gamma-interferon and interleukin-2 when stimulated with PHA, but significantly more than when unstimulated (p < 0.05). There was no difference in production of these cytokines by IEL from control or inflammatory bowel disease.